Thae use of microfluic spinning fiber as an ophthalmology suture showing the good anastomotic strength control - Park, DoYeun; Yong, In Sung; Cho, Kyong Jin; Cheng, Jie; Jung, Youngmee; Kim, Soo Hyun; Lee, Sang-Hoon (NATURE PUBLISHING GROUP, 2017)
Adjusting the mechanical strength of a biomaterial to suit its intended application is very important for realizing beneficial outcomes. Microfluidic spinning fiber have been attracting attention recently due to their various advantages, but their mechanical strength has unfortunately not been a subject of concentrated research, and this lack of research has severely limited their applications. In the current work, we showed the mechanical properties of microfibers can be tuned easily and provided a mathematical explanation for how the microfluidic spinning method intrinsically controls the mechanical properties of a microfluidic spinning fiber. But we were also able to adjust the mechanical properties of such fibers in various other ways, including by using biomolecules to coat the fiber or mixing the biomolecules with the primary component of the fiber and by using a customized twisting machine to change the number of single microfiber strands forming the fiber. We used the bundle fiber as an ophthalmology suture that resulted in a porcine eye with a smoother post-operative surface than did a nylon suture. The results showed the possibility that the proposed method can solve current problems of the microfibers in practical applications, and can thus extend the range of applications of these microfibers.
Keywords: MECHANICAL-PROPERTIES; TISSUE; MICROFIBERS; SCAFFOLDS; ASTIGMATISM; TENSILE; PROFILE